Pulsed Field Ablation in Patients With Persistent Atrial Fibrillation - Reddy, Vivek Y; Anic, Ante; Koruth, Jacob; Petru, Jan; Funasako, Moritoshi; Minami, Kentaro; Breskovic, Toni; Sikiric, Ivan; Dukkipati, Srinivas R; Kawamura, Iwanari; Neuzil, Petr (Journal of the American College of Cardiology, 2020)
BACKGROUND: Unlike for paroxysmal atrial fibrillation (AF), pulmonary vein isolation (PVI) alone is considered insufficient for many patients with persistent AF. Adjunctive ablation of the left atrial posterior wall (LAPW) may improve outcomes, but is limited by both the difficulty of achieving lesion durability and concerns of damage to the esophagus-situated behind the LAPW. OBJECTIVES: This study sought to assess the safety and lesion durability of pulsed field ablation (PFA) for both PVI and LAPW ablation in persistent AF. METHODS: PersAFOne is a single-arm study evaluating biphasic, bipolar PFA using a multispline catheter for PVI and LAPW ablation under intracardiac echocardiographic guidance. A focal PFA catheter was used for cavotricuspid isthmus ablation. No esophageal protection strategy was used. Invasive remapping was mandated at 2 to 3 months to assess lesion durability. RESULTS: In 25 patients, acute PVI (96 of 96 pulmonary veins [PVs]; mean ablation time: 22 min; interquartile range [IQR]: 15 to 29 min) and LAPW ablation (24 of 24 patients; median ablation time: 10 min; IQR: 6 to 13 min) were 100% acutely successful with the multispline PFA catheter alone. Using the focal PFA catheter, acute cavotricuspid isthmus block was achieved in 13 of 13 patients (median: 9 min; IQR: 6 to 12 min). The median total procedure time was 125 min (IQR: 108 to 166 min) (including a median of 28 min [IQR: 25 to 33 min] for voltage mapping), with a median of 16 min (IQR: 12 to 23 min) fluoroscopy. Post-procedure esophagogastroduodenoscopy and repeat cardiac computed tomography revealed no mucosal lesions or PV narrowing, respectively. Invasive remapping demonstrated durable isolation (defined by entrance block) in 82 of 85 PVs (96%) and 21 of 21 LAPWs (100%) treated with the pentaspline catheter. In 3 patients, there was localized scar regression of the LAPW ablation, albeit without conduction breakthrough. CONCLUSIONS: The unique safety profile of PFA potentiated efficient, safe, and durable PVI and LAPW ablation. This extends the potential role of PFA beyond paroxysmal to persistent forms of AF. (Pulsed Fields for Persistent Atrial Fibrillation [PersAFOne]; NCT04170621).
Keywords: posterior wall; Humans; esophagus; lidé středního věku; venae pulmonales; Electrocardiography; následné studie; Female; Aged; pulmonary vein isolation; výsledek terapie; senioři; lidé; Atrial Fibrillation; katetrizační ablace; catheter ablation; ženské pohlaví; Male; Middle Aged; persistent atrial fibrillation; Pulmonary Veins; Treatment Outcome; pulsed field ablation; srdeční katetrizace; Cardiac Catheterization; mužské pohlaví; Catheter Ablation; Follow-Up Studies; fibrilace síní; elektrokardiografie